Effect of Saline Nasal Irrigation in Patients with Sinonasal Symptoms - Widuri, Asti; Fakhriani, Rizka; Daniswara, Deoni (Majalah Kedokteran Bandung, 2024)
Nasal irrigation with saline is frequently used as an alternative therapy for sinonasal diseases since it effectively reduces sinonasal symptoms and improves the quality of life when measured by various subjective instruments. The mechanisms of action of saline irrigation remain unclear, but some hypotheses attribute the direct physical cleansing of thick mucus, allergens, and pollutants. This study aimed to determine the effect of nasal saline irrigation on the nasal mucosa using the modified Lund-Kennedy endoscopic score as the objective evaluation. This pre-post-experimental study was conducted at PKU Muhammadiyah Gamping Hospital Yogyakarta, Indonesia, from May to June 2023. The study included 18 individuals presenting with sinonasal symptoms. Participants meeting the inclusion and exclusion criteria who provided informed consent were trained in nasal saline irrigation. Patients were assessed at baseline and one week after nasal saline irrigation using endoscopy, TNSS, and MCC time. Results revealed that the mean of endoscopic scores before and after saline irrigation were 6.89±1.1 and 5.33±1.4, respectively (p-value 0.006),  while the mean of TNSS scores before and after saline irrigation was 6.17±2.3 and 4.28±2.6, respectively (p-value 0.006). Thus, nasal saline irrigation significantly improves the endoscopy and TNSS scores, but not the MCC time.